Bridging Food Studies - Goszczyński, Wojciech (Eastern European Countryside, 2024)
David Goodman, Melanie Dupuis, Michael Goodman, Alternative Food Networks: Knowledge, Practice and Politics, Rutledge, 2014, 308 pp.